Crossmodal interactions between audition and taste: A systematic review and narrative synthesis. (April 2023) - Guedes, David; Vaz Garrido, Margarida; Lamy, Elsa; Pereira Cavalheiro, Bernardo; Prada, Marília
Highlights: This review found 60 articles examining the interplay of audition and taste. Basic tastes are crossmodally associated with sounds (e.g., musical notes, music) Auditory stimuli (e.g., soundscapes, music) influence taste perception. Abstract: Taste perception results from integrating all the senses. In the case of audition, research shows that people can associate certain auditory parameters (e.g., pitch) with basic tastes. Likewise, the surrounding sonic environment (e.g., noise, music) may influence individuals' evaluation of the taste attributes of foods and drinks. This paper presents the first pre-registered systematic examination of the literature on the crossmodal interactions between audition and taste. For that purpose, four indexing services (EBSCOhost, SCOPUS, Web of Science, and PubMed) were searched using three sets of keywords on the crossmodal interactions between audition and basic tastes. Empirical, quantitative studies with healthy subjects in field, lab, or online settings were considered for inclusion. A total of 2484 records ( n  = 1481 after removing duplicates) were subject to abstract and title screening, followed by a full-text screening ( n  = 79). Sixty articles, reporting 94 eligible studies, were reviewed. Results suggest that taste may be crossmodally associated with a) pitch and musical instruments; b) words, nonwords, and speech sounds; and c) music and soundtracks. Moreover, the reviewed evidence supports the employment of auditory stimuli in the context of taste modulation, specifically in the case of a) familiar music; b) custom soundtracks, and c) noise, tones, and soundscapes. Overall, this review provides a comprehensive outlook on the multisensory interactions between audition and taste. The results show that audition has a relevant contribution to taste perception with important implications for how foods and drinks are perceived. The theoretical and practical implications of these findings are discussed.